Targeting elevated left ventricular end-diastolic pressure following primary percutaneous coronary intervention for ST-segment elevation myocardial infarction – a phase one safety and feasibility study. Issue 7 (1st October 2020) - Khan, Arshad A; Davies, Allan J; Whitehead, Nicholas J; McGee, Michael; Al-Omary, Mohammed S; Baker, David; Bhagwandeen, Rohan; Renner, Ian; Majeed, Tazeen; Hatton, Rachael; Collins, Nicholas J; Attia, John; et al.
Abstract : Introduction: Elevated left ventricular end diastolic pressure (LVEDP) is an independent predictor of mortality and heart failure in patients with ST-segment elevation myocardial infarction (STEMI). Whether lowering elevated LVEDP improves outcomes remains unknown. Methods: This non-randomized, single blinded study with prospective enrolment and sequential group allocation recruited patients undergoing primary percutaneous coronary intervention for STEMI with LVEDP ⩾ 20 mmHg measured immediately after primary percutaneous coronary intervention. The intervention arm ( n =10) received furosemide 40 mg intravenous bolus plus escalating doses of glyceryl trinitrate (100 µg per min to a maximum of 1000 µg) during simultaneous measurement of LVEDP. The control group ( n =10) received corresponding normal saline boluses with simultaneous measurement of LVEDP (10 readings over 10 min). Efficacy endpoints were final LVEDP achieved, and the dose of glyceryl trinitrate needed to reduce LVEDP by ⩾ 20%. Safety endpoint was symptomatic hypotension (systolic blood pressure < 90 mmHg). Results: From 1 April 2017 to 23 August 2017 we enrolled 20 patients (age: 64±9 years, males: 60%, n =12, anterior STEMI: 65%, n =13). The mean LVEDP for the whole cohort ( n =20) was 29±4 mmHg (intervention group: 28±3 mmHg vs . control group: 31±5 mmHg; p =0.1). The LVEDP dropped from 28±3 to 16±2 mmHg in the glyceryl trinitrate + furosemide group ( p <0.01) but remained unchanged in the control group. The median dose of glyceryl trinitrate required to produce ⩾ 20% reduction in LVEDP in the intervention group was 200 µg (range: 100–800). One patient experienced asymptomatic decline in systolic blood pressure to below 90 mmHg. There was no correlation between LVEDP and left ventricular ejection fraction. Conclusion: The administration of glyceryl trinitrate plus furosemide in patients with elevated LVEDP following primary percutaneous coronary intervention for STEMI safely reduces LVEDP.